Активність окисних ферментів у вегетативних органах ґрунтопокривних рослин за умов дії полютантів - Martynova, N.V.; Lykholat, Yu.V.; Opanasenko, V.F. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
Data about activity of superoxidedismutase and peroxidase in vegetative parts of ground cover plants in the technogenic pollution conditions have been given. Changes of enzyme activity are studied depending on a kind of pollutants. Conclusions concerning stability of plants to the action of industrial stress are drawn.